Intersector technology cooperation hard myths, soft facts - Geisler, Eliezer
Intersector or cross-sector technology cooperation has lately gained increased public and academic attention as perhaps an effective means to promote corporate global competitiveness. As empirical research continues to emerge, the widely held myths associated with such cooperation may now be challenged. This paper lists three general myths and two myths for each type of cross-sector technology cooperation : university, industry, university-government, and industry-government. These myths, some positive, others negative, tend to oversimplify the causes that contribute to the success or failure of the cooperation. The paper concludes that intersector cooperation is feasible and produces some results that benefit all the cooperating parties. However, it is also a complex phenomenon that cannot and should not be reduced to overly simplistic assertions, usually encapsulated in myths about its feasibility.
The author examines the various myths surrounding the virtues of cross-sector technology cooperation and finds that they tend to oversimplify causes which contribute to success or failure. The author suggests that intersector cooperation is possible but is a much more complex phenomenon that is generally appreciated.
Keywords: Cross-sector technology